Determination of the antioxidant activity of surface treated PET films coated with natural extracts - Farghal, Hebatullah Hassan (AUC Knowledge Fountain, 2016)
Food oxidation is one of the major concerns that food producers and consumers face. In that regard, we are developing antioxidant polyethylene terephthalate (PET) filmthat could be employed for packaging fish products. Commercial PET films were surface treated and subsequently coated with either rosemary or clove extracts. Surface treatments involveda) corona treatment and b) chemical modification which are industrial means of surface treatment; Plasma treatment, at laboratory scale, was also used.Radical scavenging activities (RSA) of both pure plant extracts and coated film extractsweremeasured using the 2,2- Diphenyl-1-Picryl Hydrazyl(DPPH) method. Treated films coated with rosemary showed %RSA of 25.6%, 22.4% and 24.1% pertaining to plasma, chemical modification and corona treated films at 1402 ppm respectively and AE values of 0.35, 0.26 and 0.28 respectively, whilepure rosemaryextract showed %RSA of 16.03% and AE value of 0.19. As for the treated films that were coated with clove, it showed %RSA of 25.0%, 25.22% and 25.15% for plasma, chemical modification and corona treatments at 1402 ppm respectively and AE values of 0.31, 0.32 and 0.33 respectively, while the plantextract showed %RSA of 47.62% and AE value of 0.72. Thiobarbituric acid (TBA) antioxidant testwas also performed on fish muscle wrapped in all types of filmswhich all showed a remarkable decrease in the degree of fish oxidationranging between 50 to 80%. All TBA tests were terminated on day 6 of storage which is in accordance with the end of the product microbiological shelf life, where TVC reached the borderline of 7 log cfu/g. Contact angle measurements confirmedthat chemicallymodifiedfilms have the highest adhesion power followed by corona then plasmatreated films. Scanning electron microscopy(SEM) results supported contact angle measurements where chemically modified films showed the roughest surface followed by corona then plasma treated films. X-ray photoelectron spectroscopy (XPS) measurements also revealedthat chemicallymodified filmsresulted in the formation of a higher concentration of oxygen containing functional groups on the PET surface as compared to other treatments, indicative of the highest surface adhesion capacity of the chemically modified film. Finally, the oxygen permeability of chemically modified PET films was the same as untreated films which is an indication that treatment did not affect film barrier properties.